Polemik Penataan Kota: Tinjauan Yuridis terhadap Pelaksanaan Relokasi Warga Bantaran Sungai Banjir Kanal Kota Semarangdalam Proyek Normalisasi - Suwandi, Dedy; Novrikar, Acel (Hukum dan Masyarakat Madani, 2025)
Semarang City's East Flood Canal (BKT) normalisation project aimed at flood control caused polemics when it led to the eviction of 97 families in Tambakrejo without proper relocation first. Despite an agreement facilitated by Komnas HAM in 2018 that the eviction would not be carried out until replacement housing was available, the facts on the ground showed a violation of the agreement. This phenomenon reflects the conflict between the legality of government action and the social rights of the urban poor. This research aims to review the juridical aspects of the implementation of relocation of riverbank residents in the BKT normalisation project, as well as to assess the suitability of the policy with the principles of responsive spatial law and social justice. The approach used is normative juridical with a review of laws and regulations, legal decisions, official documents, and analysis of media coverage. The results show that although the eviction action has a legal basis in Semarang City Regional Regulation No. 5/2017 on Public Order, its implementation does not consider the right to housing and procedural justice for affected residents. The government emphasises repressive rather than dialogical and solution-based approaches. The conclusion of this research states that the enforcement of spatial planning law in Semarang City has not fully reflected the principle of responsive law as idealised by Nonet and Selznick. A reformulation of urban planning policy that integrates legality with social justice is needed to protect the rights of the urban poor affected by relocation. Keywords: Canal Flood; Agrarian Law; Social Justice; River Normalisation; Forced Relocation.